2018
DOI: 10.1089/met.2018.0052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Freeze-Dried Grape Powder on High-Density Lipoprotein Function in Adults with Metabolic Syndrome: A Randomized Controlled Pilot Study

Abstract: Grape powder consumption did not impact HDL function in this cohort of adults with MetS. However, it was shown to improve fasting triglycerides, a risk factor for cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Forty-five studies were included in this systematic review, of which 18 were crossover randomised controlled trials (RCT) [27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], and 27 were parallel RCTs [26,28, (see Table 3). The sample size of both experimental and control group in the interventions ranged from 5 to 63.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Forty-five studies were included in this systematic review, of which 18 were crossover randomised controlled trials (RCT) [27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], and 27 were parallel RCTs [26,28, (see Table 3). The sample size of both experimental and control group in the interventions ranged from 5 to 63.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…J774A.1 macrophages (ATCC; Manassas, VA) were used to measure HDL CEC using radiolabeled methods as previously described. [19] PON1 arylesterase activity was measured using phenyl acetate as a substrate, as previously described. [15] PON1 lactonase activity was determined using methods reported by Millar et al [19]…”
Section: Hdl Cec and Pon1 Activity Assaysmentioning
confidence: 99%
“…Thus, 24 articles (25 datasets, 618 subjects assigned to grape juice/extract/product administration and 587 subjects assigned to placebo) were included in the final analysis [27,29,[32][33][34][35][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. In detail, 21 studies (22 data-sets) reported data on TC, 22 studies (23 datasets) on HDL-C, 20 studies (21 datasets) on TG, 20 studies (21 datasets) on LDL-C, 4 studies (4 datasets) on oxLDL-C, 2 studies (2 datasets) on apo A, 3 studies (3 datasets) on apo B.…”
Section: Resultsmentioning
confidence: 99%
“…The number of enrolled subjects varied from 8 to 50, the mean age from 20.7 to 62.0 years, and the prevalence of male gender from 0% to 100%. Eleven studies evaluated the effect of whole grape products (grape powder or pomace) [32][33][34]44,45,50,51,53,55,59,61], five studies focused on grape juice [48,49,52,56,57], seven studies on grape seed extracts [27,29,35,46,47,54,58], and one study on the effect of grape skin extracts [60].…”
Section: Study Characteristicsmentioning
confidence: 99%